A model for examining the relation between news media literacy skills, heuristic-systematic news processing and political knowledge levels - Rady, Doaa Mohamed Fathallah (AUC Knowledge Fountain, 2014)
The study aimed to test the relation between the levels of news media literacy skills, types of news processing levels, and the levels of political knowledge. Also, the study investigated the relation between news media reliance, media gratification sought and elaborative processing, and levels of political knowledge. A survey method was used among undergraduate and graduate students at the American University in Cairo. Furthermore, this research developed a scale for measuring news media literacy skills among university students. The scales' items tested on a sub sample then statistically examined through factor analysis for refining the final items of the final survey. Moreover, this research contributed to the field through proposing a new scale for assessing news media literacy skills (SNMLS) that has been derived from previous scales, with adaptation to Egyptian context and the proposed conceptual framework. The scale achieved high internal reliability.